Perencanaan Strategis Sistem Informasi Dan Teknologi Informasi Pada Sekolah Menengah Kejuruan Negeri 2 Pagar Alam - Yogi Mukti (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2017)
The development of information technology has increased so much interesting to do research, from a variety of disciplines. This study is flexible means to include all the things, one of which is the business process in an organization, HOW to create an organization that is able to compete. Obviously we need a strategic plan to improve the quality and thus the quality of the organization, what is the purpose of the organization is able to walk properly. In this case also attracted the attention of researchers is to conduct research on the organization of SMK in the city of Pagar Alam from the viewpoint of information systems and information technology. Obviously in this case we need a strategic planning / IT was good so that it can increase the quality of SMK in Pagar Alam, this research using the framework Ward and Peppard with Five Porter analysis, PEST, CSF, SWOT, to support the research.